A comparison of the pharmacokinetic and pharmacodynamic properties of nitroglycerin according to the composition of the administration set: A preliminary study. Issue 9 (March 2018) - Kim, Choon Ok; Song, Jeongyun; Min, Ji Young; Park, Su Jung; Lee, Hye Mi; Byon, Hyo-Jin
Abstract: Background: There is a risk of drug sorption into an intravenous administration set composed of polyvinyl chloride (PVC), polyurethane (PU), or polyolefin (PO). This has implications on the dose of the active ingredient the patient receives, and thus therapeutic success. This study aimed to determine the plasma concentration of nitroglycerin and the effect of nitroglycerin on patients based on the composition of the administration set. Methods: Using a randomized, open-labeled, 3 × 3 crossover method, 9 volunteers were assigned to 3 groups. In period I, nitroglycerin (100 μg/mL) was infused via a PVC- (group A), PU- (group B), or PO-based (group C) administration set. In period II, PU- (group A), PO- (group B), and PVC-based (group C) administration sets were used, and in period III, PO- (group A), PVC- (group B), and PU-based (group C) administration sets were used. The rate of drug administration in all periods was 12 mL/hour for 30 minutes using an infusion pump. Blood samples were collected, and the plasma concentrations of nitroglycerin were analyzed using validated high-performance liquid chromatography coupled with tandem mass spectrometry. Blood pressure was determined using a sphygmomanometer applied to the other upper arm at an interval of 5 minutes. Results: We observed that the mean plasma concentration of nitroglycerin over time when administered using a PO-based tube was higher than that when using a PU- or PVC-based tube. When the percent change of the mean arterial pressure from baseline at each time point was compared among groups, there were statistically significant differences between PU and PO or PVC at most points during nitroglycerin infusion. Conclusion: Our results showed higher nitroglycerin plasma concentration and lower arterial pressure when a PO-based administration set was used than when a PVC- or PU-based administration set was used. PO-based administration sets may be more appropriate for nitroglycerin administration compared to those composed of PVC or PU.